High-Q fano resonances via direct excitation of an antisymmetric dark mode - Bochkova, Elena (2020)
The engineering of metal-insulator-metal metasurfaces (MSs) displaying sharp spectral features based on Fano-type interference between a symmetric bright mode and an antisymmetric dark mode is reported. The proposed mechanism for direct excitation of antisymmetric mode avoids the necessity of mode hybridization through near-field coupling. Modeling and experimental results bring evidence that such MSs operating in the microwave or terahertz domains provide greater flexibility for Fano resonance engineering and provide strong enhancement of the spectral selectivity factor. It is shown that the occurring Fano resonance interference is related to the broken eigenmode orthogonality in open systems and is independent of hybridization mechanism.